2014
DOI: 10.1097/coc.0b013e31826e071b
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib Combined With Stereotactic Radiosurgery in Previously Treated Patients With Advanced Non–Small Cell Lung Cancer

Abstract: The SBRT combined with gefitinib is a promising treatment strategy for advanced (stage IIIb or IV) NSCLC after the failure of previously chemotherapy. This method improves local control and disease-related symptoms with tolerated toxicity, and even increases the progression-free survival and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Although only one patient was treated with SBRT to the lung, local therapy was associated with a median time to progression of 10 months and a median survival time of 41 months. Finally, Wang et al 23 treated 14 NSCLC patients (not limited to EGFR-mutant disease) with disease progression after platinum-based chemotherapy with gefitinib and SBRT directed at progressive metastatic disease. The 1-year local control and overall survival rates were 83.9% and 69.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although only one patient was treated with SBRT to the lung, local therapy was associated with a median time to progression of 10 months and a median survival time of 41 months. Finally, Wang et al 23 treated 14 NSCLC patients (not limited to EGFR-mutant disease) with disease progression after platinum-based chemotherapy with gefitinib and SBRT directed at progressive metastatic disease. The 1-year local control and overall survival rates were 83.9% and 69.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these studies reveal a potential role for the addition of metastasis-directed SBRT in improving disease control and PFS in stage IV EGFR-mutant NSCLC patients treated with TKI. [21][22][23] This study has the typical limitations of a retrospective analysis including a relatively small number of patients and potential for selection bias. Our findings, which should be viewed as hypothesis generating, suggest that consolidation SBRT with continued TKI therapy has the potential to alter the natural history of disease progression and extend the PFS and overall survival of a subset of patients with stage IV EGFR-mutant NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding extra-cranial SRT, the prospective study of Wang et al used SRT to treat a maximum of 3 lung metastases in stage IV NSCLC patients (n = 14) with concurrent gefitinib [51]. Grade 3 toxicity possibly caused by the concurrent treatment occurred in 4 patients (29%), consisting of stomatitis, esophagitis, and radiation pneumonitis (n = 3) ( Table 2).…”
Section: Egf-r-inhibitors (Gefitinib Erlotinib Lapatinib)mentioning
confidence: 99%
“…The main advantage of SBRT is its short radiation time and less damage to the surrounding tissues, resulting in a decreased risk of radiation pneumonitis in lung cancer. Wang et al (15) reported that in 14 patients with advanced NSCLC, SBRT combined with gefitinib resulted in a disease remission rate of up to 57.1%. The median time of disease remission was 8 months, while the 1-year survival rate was 69.6%, suggesting that this regimen may improve local control and disease remission rates with few side effects.…”
Section: Discussionmentioning
confidence: 99%